2012
DOI: 10.4314/sajas.v42i3.8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary L-threonine and <i>Saccharomyces cerevisiae</i> on performance, intestinal morphology and immune response of broiler chickens

Abstract: The objective of this study was to investigate the effects of four dietary levels of L-threonine (0, 2.5, 5 and 7.5 g/kg) with or without Saccharomyces cerevisiae (SC) on performance, carcass characteristics, intestinal morphology and immune system of broiler chickens. A total of 360 1-d-old male broiler chicks were randomly allocated to eight treatments with three replicates of 15 birds. The experiment was done at 0 to 3 weeks (as starter phase) and 3 to 6 weeks (as grower phase). Growth performance traits in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
40
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 15 publications
8
40
2
1
Order By: Relevance
“…Opposite to this results, in another experience did 2 not register changes in carcass performance in broilers fed Sc (in the same level that used here) or T (0-7.5 g/Kg food) (Rezaeipour et al, 2012). Perhaps, the different result must be attributed to the difference in Sc nature and T levels (30% vs 0.25-0.75 g/Kg feed) used in each assay.…”
Section: Resultsmentioning
confidence: 53%
See 3 more Smart Citations
“…Opposite to this results, in another experience did 2 not register changes in carcass performance in broilers fed Sc (in the same level that used here) or T (0-7.5 g/Kg food) (Rezaeipour et al, 2012). Perhaps, the different result must be attributed to the difference in Sc nature and T levels (30% vs 0.25-0.75 g/Kg feed) used in each assay.…”
Section: Resultsmentioning
confidence: 53%
“…Also, in another assay were noticed that addition of T (2.5-7.5 g/Kg food) findings, in these research, the addition of Sc alone, in the same level used on this experiment, did not modify productive variables (Rezaeipour et al, 2012). Coincidently to this results, in another research, was registered that broilers fed Sc in higher levels to use on this experience (1-3%) and noticed high Consumption but lower Weight Gain (Ahmed et al, 2015).…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…However, he also reported that increase in threonine requirements for broilers, raised in builtup litter environments to microbial challenges, because threonine involved in mucin formation and mucin control microbial communities and nutrient availability in the gut (5). The supplementation of L-threonine in broiler diet improved growth performance and intestinal morphology, by increasing crypt depth, villi height and width of jejunum and ileum segment in broilers (19). Similarly, the use of methionine and threonine in broiler diets above NRC recommendations, considered as a better nutritional strategy, to overcome unfavourable stress conditions by improving immune cells in tropical area.…”
Section: Results and Discussion Body Weight Gainmentioning
confidence: 99%